The analysis of the use of mobile technology in 6-8 years old children's literacy process - Rossetto, Alessandra Dedéco Furtado; Dutra, Alessandra (Revista Hipótese, 2017)
This study aims analyze the use of mobile technology in the literacy process of 6- 8 years of children. To accomplish this study I have utilized descriptive, field and analytical research. The results showed that the specialists agreed that the use of mobile technology might help children in their literacy process; it encourages the student’s love for reading and writing through many types of texts and tools, especially those available on the iPad or tablet applications. Although technology can help and assist the development of the literacy process, it cannot assist some specific skills in the writing process.
Keywords: mobile technology; literacy process; learning and interaction